A Case Study of Abdominal Compartment Syndrome Following Sigmoidopexy for Sigmoid Volvulus - Chishti Tanhar Bakth Choudhury; Md. Golam Afsar; Mahmudur Rahman Khandoker (Medical Research and Its Applications Vol. 4, 2024)
The detrimental effects of intra-abdominal hypertension and abdominal compartment syndrome (ACS) affect almost every system by altering organ perfusion. Intra-abdominal hypertension, in which pressure is 12 to 20 mmHg whereas ACS, in which pressure is higher than 20 mmHg. Acute coronary syndrome (ACS) is life threatening and is not very uncommon in our practice. There is a clinical scenario of 70 year male with a history of absolute constipation and abdominal distention with pain in the abdomen. He was attended at Govt. hospital ER and was diagnosed with volvulus sigmoid colon and immediate laparotomy with untwist of gut and sigmodopexy done. Closure of abdomen was done without any abdominal drain tube and the patient was attempted for extubation but did not achieve adequate % SpO2 and shifted to ICU in intubated state. Following the night of the operation, the patient’s abdomen was becoming tense and diagnosed with ACS and immediate Flatus tube and NG tube were inserted. Both tubes were kept in situ for>48 hours and the patient’s abdomen became soft and normal. This paper describes the management of the ACS, and all measures presented (NGT, flatus tube, TPN, intravenous therapy, ventilator support, etc) in combination may have produced the desirable effect for this particular patient, even if seemingly NGT and flatus tube had a decisive action.